Project Based Self-Regulated Learning as a Parenting Model to Increase the Attitude of Responsibility of Children Age 5-6 Years - Kamtini Kamtini; Damaiwaty Ray; Dorlince Simatupang; Salsabila Hasiana Tanjung; Husni Wardi Tanjung (BIRCU, 2020)
Stimulating the attitude of responsibility to the child, should the child be given tasks that the child should accomplish. The Treatment that can be given to children is by using the concept of learning model project based learning. In addition, the child is also able to regulate or control himself. So the children know and work on their duties. This is called self-regulated learning, the child is able to choose decisions and self-control, self-initiated initiatives that include goal setting and setting efforts to achieve objectives, management of time, and set Physical and social environments. This research was done to find how the project based learning role when associated with self-regulated learning in the attitude of responsibilities of children age 5-6 years. This research method uses experimental research by testing the use of project-based self-regulated learning models on the child's responsibility. Based on the test results done then it is derived that the model of project based self-regulated learning can significantly improve the attitude of children’ responsibility. The attitude of responsibility will change significantly when the treatment is repeatedly done to children.